Effect of Physical Activityon Insulin Resistance in Diabetes Mellitus - Almutawa, Aiesha Mohammed; Al Sowayan, Noorah Saleh (International Journal of Human and Health Sciences (IJHHS), 2023)
Acquiring and sustaining physical activity as part of one’s daily routine is an excellent approach to control the level of blood glucose and one’s overall health, whether healthy as well as diabetic. We give guidelines for exercise as well as its effects on insulin resistance in diabetes patients in this review, which have been supported by numerous prior studies.A collection of movements structured according to a specified protocol that boosts energy consumption is referred to as physical exercise. Exercise improves blood glucose levels in T2DM patients, lowers or eliminates risk factors for metabolic as well as cardiovascular disease, facilitates weight loss, and lowers insulin resistance.The influence of physical exercise on insulin resistance differs based on the kind, intensity, and duration of exercise, so understanding the many types of physical activity and meeting personal requirements is important. International Journal of Human and Health Sciences Vol. 07 No. 01 Jan’22 Page: 9-14